Inter-Organizational Paradox Management: How national business systems affect responses to paradox along a global value chain. Issue 4 (April 2022) - Schrage, Stephanie; Rasche, Andreas
This study discusses the relationship between inter-organizational paradox management, national business systems and global value chains. Using case study evidence from a global value chain in the footwear industry (in Germany and China), we analyse how different businesses in the chain responded to the paradoxical tension arising from the competing demands to provide a living wage to workers and to uphold financial performance. Our findings highlight organizational responses to this paradox along the value chain, showing how these responses were shaped by the interplay of different types of pressures exerted by national business systems and the value chain itself. While these pressures were aligned in the German part of the chain, they were not aligned on the Chinese side. The study makes two contributions: (1) we develop a taxonomy outlining how the alignment of different types of pressures influences whether organizations choose either proactive or defensive paradox management; and (2) we argue that theorizing the impacts of cross-national distance on paradox management can be enhanced by adopting a multidimensional approach to institutional variety that extends beyond culture-based arguments.